2016
DOI: 10.1016/j.forpol.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Assessing awareness of tree pests and pathogens amongst tree professionals: A pan-European perspective

Abstract: (M. Marzano). 2 Highlights• We conducted a questionnaire survey of tree professionals in 9 European countries.• Self-reported awareness levels of pests amongst tree professionals is low.• Awareness increases with age and frequency of visits or familiarity with forests.• Resource pressures and perceived behaviours of others act as barriers to change.• Approaches to raising awareness should include knowledge brokerage. AbstractTree professionals play an important role in protecting forests against invasive pests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…Fuller et al 2016;Marzano et al 2016;McFarlane et al 2006), our findings indicate generally low levels of awareness and knowledge of tree pests and diseases, but higher levels of stated concern. This may reflect a tendency for people to be more concerned about unfamiliar risks or those they know little about, risks that may have effects that are delayed in time and where there is scientific uncertainty (Renn 2008;Slovic et al 1980;Williamson and Weyman 2005).…”
Section: Discussionmentioning
confidence: 60%
“…Fuller et al 2016;Marzano et al 2016;McFarlane et al 2006), our findings indicate generally low levels of awareness and knowledge of tree pests and diseases, but higher levels of stated concern. This may reflect a tendency for people to be more concerned about unfamiliar risks or those they know little about, risks that may have effects that are delayed in time and where there is scientific uncertainty (Renn 2008;Slovic et al 1980;Williamson and Weyman 2005).…”
Section: Discussionmentioning
confidence: 60%
“…In their study of forestry professionals in South Africa, Hurley et al (2012) found that general levels of awareness of tree pests was relatively high, but they were lower in relation to specific pests. A survey of 392 tree professionals across nine European countries also reported relatively modest levels of awareness of tree pests (Marzano et al 2016). Out of the six pests listed, just over half (51.4%) stated that they had little or no awareness of these pests.…”
Section: Awareness Levels Of Tree Pest and Diseases And Behavioursmentioning
confidence: 99%
“…Behaviours listed mostly include actions such as plant buying habits (not importing plants, buying from accredited sources), cleaning footwear and equipment and citizen science activities. For example, 88% of tree professionals in nine European countries said they preferentially buy plants from an accredited source; 77% would avoid bringing in plants from abroad but only 65% said they would clean footwear, vehicles and bike tyres after visiting parks, gardens and woodlands (Marzano et al 2016). Respondents from the 'People's Panel' in Auckland stated that, in addition to cleaning stations, they had cleaned boots and equipment at home (34%) and informed family and friends about kauri dieback (32%).…”
Section: Awareness Levels Of Tree Pest and Diseases And Behavioursmentioning
confidence: 99%
“…However, invasive tree pests and diseases are increasingly impacting natural resources and the benefits and services they provide. Research on the social dimensions of tree health has provided a range of insights into the risk perceptions, decision-making and behaviors of owners and managers of woodlands and forests [7][8][9]. Research suggests that biosecurity actions depend on: the range of values and beliefs structuring attitudes and willingness to act or to accept pest control and management measures [10,11]; assessments of risk, how these are socially mediated and resulting trade-offs [12,13]; whether advice about control and management and the need for action is considered to be "legitimate" or come from a legitimate source [10]; a belief in the control or management option actually being effective [14]; and, being able to assign responsibility for management [15].…”
mentioning
confidence: 99%